RHIZOMATIC APPROACH TO THE 21ST CENTURY EFL LEARNING: A LITERATURE REVIEW - Nizar Ibnus (IAIN Syekh Nurjati Cirebon, 2022)
21st-century education is focused on preparing students with certain learning and life skills. Rhizomatic learning is among learning approaches subject to 21st-century challenges. This study is aimed at exploring what rhizomatic learning has to offer and what the underpinning theories are. The study employed a literature review procedure including writing, summarizing, integrating, analyzing, and criticizing. Rhizomatic learning is identified with a more modifiable instructional design central to students' needs. By principle, rhizomatic learning corroborates with peer scaffolding to promote collaboration and is feasible to be carried out through flipped classrooms by incorporating higher-order thinking activities. To avoid being lost in the information search process as well as to make students focused on constructing new knowledge, a teacher's intervention is required through guided inquiry.